An outbreak of Clostridioides difficile infections due to a 027-like PCR ribotype 181 in a rehabilitation centre: Epidemiological and microbiological characteristics. (October 2020) - Kachrimanidou, Melina; Baktash, Amoe; Metallidis, Symeon; Tsachouridou, Οlga; Netsika, Foteini; Dimoglou, Despoina; Kassomenaki, Angeliki; Mouza, Eirini; Haritonidou, Mina; Kuijper, Ed
Abstract: Clostridioides difficile is one of the most important healthcare-associated pathogens. Recently, several new 027-like types have been found that all belong to the multilocus sequence typing (MLST) Clade 2. We report a rapidly spreading outbreak of C. difficile infections (CDI) due to a newly identified PCR ribotype (RT) 181 in a Rehabilitation Centre (RC). Genomic analysis revealed the outbreak strain, not previously identified in Greece, belonged to clade 2, sequence type (ST) 1 and had a 18bp deletion in tcdC at position 311 together with a single nucleotide deletion at position 117, similarly to RT 027. The presence of a clonal outbreak was confirmed by whole genome sequencing, yet the source of this ribotype remained unclear. The emergence and rapid spread of new C. difficile ribotypes highlights the need for ongoing C. difficile surveillance and better understanding of overall Clade 2 phylogeny. Highlights: A rapid spread of a newly identified PCR ribotype 181. Genomic analysis revealed a clonal outbreak of a clade 2 strain. Need for better understanding of overall Clade 2 phylogeny.